2015
DOI: 10.1179/1743281215y.0000000024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CaO/Al2O3ratio on viscosity and crystallisation behaviour of mould flux for high Al non-magnetic steel

Abstract: In order to facilitate the development of CaO-Al 2 O 3 based mould flux for casting high aluminium, non-magnetic steel, the effect of CaO/Al 2 O 3 ratios from 0.6 to 3.2 on viscosity and crystallisation characteristics were investigated with the aid of a rotational viscometer, Fourier transform infrared spectroscopy, a single hot thermocouple technique and X-ray diffraction analysis. The results showed that, at temperatures above 1543 K (12708C), the viscosity first decreased and then became stable with increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 16 publications
4
20
0
Order By: Relevance
“…Thus, the degree of weight loss reflects the reduction degree of iron ore oxides. Reduction degree of copper slag was calculated as follows: 25,26) Δ A t , Δ B t , Δ C t are weight loss of sample A, B and C (as shown in Fig. 8).…”
Section: Apparatus and Methodsmentioning
confidence: 99%
“…Thus, the degree of weight loss reflects the reduction degree of iron ore oxides. Reduction degree of copper slag was calculated as follows: 25,26) Δ A t , Δ B t , Δ C t are weight loss of sample A, B and C (as shown in Fig. 8).…”
Section: Apparatus and Methodsmentioning
confidence: 99%
“…Adapted from published literature. 53,54,57,66,[87][88][89]93) 8 wt% CaF 2 and NaF have similar effects on depolymerizing the slag network, which lowers the viscosity and improves the diffusion kinetics to accelerate the formation of the primary cuspidine phase during cooling. However, the reactions of CaF 2 and NaF with SiO 2 and the volatilization of the fluorides at high temperatures may result in other operational problems at the casters that would need to be considered.…”
Section: Flux Developments For High-al Steelsmentioning
confidence: 99%
“…As the amphoteric behavior of Al 2 O 3 , a large discrepancy in the effect of Al 2 O 3 on viscosity was found in different slag systems. [39,44,46,[59][60][61][62][63] The results regarding the effect of BaO and MgO content on viscosity and structure of the CaO-Al 2 O 3 -based mold fluxes system suggested that BaO works in a complicated fashion since it has a strong charge compensation effect on the [AlO 4 ] 5tetrahedron, while the addition of MgO tends to decrease the viscosity of the slag melt because the free O 2ions from MgO depolymerize the network structure, which leads to the reduction of melt flow resistance and apparent activation energy. [64,65] Moreover, the viscosity of CaO-Al 2 O 3 -based mold fluxes decreased with the increasing TiO 2 content, and the Raman spectral results revealed that the degree of polymerization is reduced by increasing TiO 2 .…”
Section: Mold Fluxes With Low Sio 2 Contentmentioning
confidence: 99%